How many object colors can we distinguish?. Issue 5 (6th July 2015) - Kuehni, Rolf G.
Abstract: The question of how many different colors humans can perceive has been of interest to philosophers, psychologists and color scientists for centuries. In recent years the question of the number of distinguishable object color stimuli has been addressed by color scientists by defining a distinguishable color as a given stimulus surrounded by the contour of stimuli just noticeably different from the central stimulus. For a particular set of conditions the number of distinguishable object color stimuli assessed in this manner has recently been found to be slightly larger than 2 million. In this article an argument is made that the related rules are arbitrary and unnecessarily limiting. Based on logical arguments and experimental just noticeable difference data it is shown that, for the conditions involved, a more realistic if conservative number of distinguishable object color stimuli is ∼40 million. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 439–444, 2016